(untitled) (Physical Education, Health and Social Sciences, 2025)
This study explores the influence of wearable technology on athlete motivation, with a specific focus on the role of real-time feedback. As wearable devices such as smartwatches, fitness trackers, and heart rate monitors become increasingly integrated into sports training, understanding their psychological impact is essential. Grounded in Self-Determination Theory, the study investigates how wearable tech affects intrinsic and extrinsic motivation, goal-setting behaviors, and training consistency. A quantitative research design was employed, involving 100 amateur and semi-professional athletes aged 18–35 who regularly use wearable devices. Data were collected using the BREQ-3 motivation scale and a custom survey assessing wearable use and perceived impact. Descriptive and inferential statistics were applied, including Pearson correlation and independent samples t-tests. Findings indicate a moderate positive correlation between wearable use and intrinsic motivation, and a high percentage of athletes reported that real-time feedback supported their goal setting and training adherence. While some extrinsic motivation was present, intrinsic motivation remained the dominant driver. No significant gender differences in motivation levels were found. The study concludes that wearable technology can enhance athletic motivation, especially when used to support autonomy and self-improvement. However, caution is advised to avoid over-reliance on external metrics. The results have practical implications for athletes, coaches, and technology developers seeking to optimize the psychological benefits of performance tracking tools.